2013
DOI: 10.1186/cc12517
|View full text |Cite
|
Sign up to set email alerts
|

Serum adipocyte fatty acid-binding protein in the critically ill

Abstract: Sepsis due to unabated inflammation is common. Increased production of pro-inflammatory cytokines, free radicals, and eicosanoids has been detected in sepsis and other critical illnesses but could also be due to decreased synthesis and release of anti-inflammatory molecules. Increased serum adipose-fatty acid-binding protein (A-FABP) levels can cause insulin resistance and have been reported in the critically ill, serve as a marker of prognosis, and thus link metabolic homeostasis and inflammation. A-FABP can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The gene encoding this adipokine is located on chromosome 8q21. Elevated levels of FABP4 are closely linked with the development of obesity, IR, DM, hypertension, CAD and atherosclerosis [10, 14, 15]. Studies in humans have shown that a genetic variant at the FABP4 locus reduced the risk for atherosclerosis, diabetes and coronary heart disease [16, 17], and reduced FABP4 expression in adipose tissue was related to lower risk for CAD and DM [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene encoding this adipokine is located on chromosome 8q21. Elevated levels of FABP4 are closely linked with the development of obesity, IR, DM, hypertension, CAD and atherosclerosis [10, 14, 15]. Studies in humans have shown that a genetic variant at the FABP4 locus reduced the risk for atherosclerosis, diabetes and coronary heart disease [16, 17], and reduced FABP4 expression in adipose tissue was related to lower risk for CAD and DM [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in humans have shown that a genetic variant at the FABP4 locus reduced the risk for atherosclerosis, diabetes and coronary heart disease [16, 17], and reduced FABP4 expression in adipose tissue was related to lower risk for CAD and DM [16]. Several studies have proved that increased circulating FABP4 levels are a promising biomarker predicting heart failure, stroke, and prognosis and mortality in patients with end-stage renal disease, CAD or other critical illnesses [6, 14, 15, 20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Adipose-fatty acid binding protein (A-FABP), which induces insulin resistance and whose levels are increased in the critically ill [ 18 ], is a carrier of fatty acids and is expressed primarily in adipocytes and macrophages. A-FABP regulates systemic insulin sensitivity and lipid and glucose metabolism [ 19 ]. Mice deficient in A-FABP are resistant to the development of hyperinsulinemia, hyperglycemia and insulin resistance [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A very important aspect is that the CD4+ T helper cells use the major histocompatibility complex class II (MHC II) for antigen recognition [24][25][26]. Following the biomacromolecular and cellular reactions, increased amounts of proinflammatory cytokines are released, such as tumor necrosis factor alpha (TNF-α), interleukin-1 (IL-1), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6) [27][28][29]. The released pro-inflammatory mediators enter a vicious circle, leading to the activation and proliferation of leucocytes, the overexpression of the endothelial adhesion molecules, the activation of the complement system, and to the overproduction of tissue factors and free radicals (FR) [30].…”
Section: Pathophysiological and Clinical Aspects In Sepsismentioning
confidence: 99%